Institutionalising Patents in Nineteenth-Century Spain - Pretel, David (Palgrave Studies in Economic History, 2018)
This book examines the development of the Spanish patent system in the years 1826 to 1902, providing a fundamental reassessment of its evolution in an international context. The Spanish case is particularly interesting because of this country's location on the so-called European periphery and also because of the centrality of its colonial dimension. Pretel gauges the political regulation and organisation of the system, showing how it was established and how it evolved following international patterns of technological globalisation and the emergence of the 'international patent system' during the late nineteenth century. Crucially, he highlights the construction and evolution of the patent system in response to the needs of Spain's technologically dependent economy. The degree of industrial backwardness in mid-nineteenth-century Spain set the stage for the institutionalisation of its modern patent system. This institutionalisation process also entailed the introduction of a new technological culture, social infrastructure and narrative that supported intellectual property rights. This book is important reading to all those interested in the history of patents and their role in globalisation. David Pretel is Research Fellow at the Centre for Historical Studies, Colmex, The College of Mexico, Mexico. He specialises in the global history of technology, international economic history and the intellectual history of capitalism.